Development of apparatus to provide immediate accurate feedback to sprinters in the normal training environment - Sprint start apparatus - Sanderson, L. K.; McClements, J. D.; Gander, R. E.
Presentation of the sprint start apparatus being developed at the University of Saskatchewan to provide immediate kinetic, kinematic and temporal feedback in an ecologically valid normal training environment has been shown to produce valid accurate data. Preliminary research has been done which indicates that the apparatus can provide an indication of the most important factors of the sprint start. A great deal of further research must be done. The most important implication of this work is the ability to provide valid accurate immediate feedback to the athlete and coach in the normal training environment.